The development, functions, and challenges of Internet centres before and during the covid-19 Pandemic era: A case study on the northwest Coast of Sabah - Halina Sendera Mohd Yakin; Junaidah Januin (Human Resource Management Academic Research Society (HRMARS), 2024)
This study thoroughly examines the development and advancement of Internet centres in Malaysia, with a specific focus on the Northwest Coast of Sabah and their roles and challenges during the COVID-19 pandemic. Utilising a comprehensive mixed-methods research approach, including participatory observation, text analysis, questionnaires, and in-depth interviews, the research engaged 13 informants and 133 diverse respondents. The compelling findings clearly show that Malaysia's Internet centres, established through long-term government plans in collaboration with various entities, were well-established before the pandemic and effectively achieved their intended objectives. However, critical issues such as limited awareness of their presence and remote locations have significantly hindered their effectiveness as practical communication tools and drivers of community socioeconomic development. During the pandemic, these centres struggled to fulfil their role as providers of free internet services and devices, greatly impacting residents who depend on them for virtual activities. The study conclusively presents strong recommendations aimed at optimizing digital communication and Internet centres to enhance rural community socioeconomic development and digital integration into the national landscape.